2018
DOI: 10.1021/acs.inorgchem.8b00072
|View full text |Cite
|
Sign up to set email alerts
|

Palladium(II)-Stabilized Pyridine-2-Diazotates: Synthesis, Structural Characterization, and Cytotoxicity Studies

Abstract: Well-defined diazotates are scarce. Here we report the synthesis of unprecedented homoleptic palladium(II) diazotate complexes. The palladium(II)-mediated nitrosylation of 2-aminopyridines with NaNO results in the formation of metal-stabilized diazotates, which were found to be cytotoxic to human ovarian cancer cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 50 publications
3
12
0
Order By: Relevance
“…The N–Se distance for 3 – 10 was in the interval between 1.824(3) Å and 1.860(4) Å, and was typical for the N–Se single bond. The C=N separation (1.25(1)–1.291(5) Å for 3 – 10 ) corresponded to a typical double bond [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…The N–Se distance for 3 – 10 was in the interval between 1.824(3) Å and 1.860(4) Å, and was typical for the N–Se single bond. The C=N separation (1.25(1)–1.291(5) Å for 3 – 10 ) corresponded to a typical double bond [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…Recently we demonstrated that 2-pyridylselenenyl halides selectively react with a broad scope of nitriles to form adducts 3-14 in excellent yields (Scheme 1) [11,29]. Within this work, following our interest in CN and NN triple bond activation [30][31][32][33][34][35][36][37][38][39][40][41][42][43], we attempted to prepare analogous Te derivatives. 2-Pyridyltellurenyl bromide (16 was easily synthesized by the oxidation of di-(2-pyridyl)-ditelluride with molecula bromine.…”
Section: Resultsmentioning
confidence: 99%
“…The amine N atom is significantly flattened due to conjugation with a vinyl group, the C1-S1-N1-C13 torsion angle being 28.46 (13) . The N1-C13 bond distance [1.4138 (13) Å ] is slightly shorter than that of a standard C-N single bond in similar compounds (Tskhovrebov et al, 2012(Tskhovrebov et al, , 2014(Tskhovrebov et al, , 2018Repina et al, 2020). The molecular structure features an intramolecular S1 O4Á Á ÁH12B-C12 hydrogen bond (Table 1), leading to the formation of an S(13) macrocycle in the crystal.…”
Section: Structural Commentarymentioning
confidence: 98%